Fear and perceived likelihood of victimization in the traditional and cyber settings - Jeske, Debora (2014)
This study considers the influence of perceived likelihood, demographics (gender and education) and personality on fear of victimization and cyber-victimization using a survey design (N=159). The results suggest that perceived likelihood of victimization predicts fear of victimization in traditional contexts. Women tend to be more fearful of victimization in traditional and cyber contexts, confirming previous research. No group differences emerged in relation to education. Self-esteem and self-efficacy were not significant predictors of fear or perceived likelihood of victimization. However, perceived likelihood was a significant predictor of fear of victimization in traditional settings. This may suggest that different variables (such as awareness of vulnerability) may play a role in fear of victimization in cyber settings. Further group comparisons revealed that fear of victimization and cybervictimization depended on whether or not participants reported high or low perceived likelihood of victimization and internet use. Higher internet use was associated with greater fear of victimization, especially in combination with greater perceived likelihood of victimization. This may suggest an exposure effect, in that being online more frequently may also increase awareness of cyber incidents